Analyzing rare diseases terms in biomedical terminologies - Pasceri, Erika (JLIS.it, 2012)
Rare disease patients too often face common problems, including the lack of access to correct diagnosis, lack of quality information on the disease, lack of scientific knowledge of the disease, inequities and difficulties in access to treatment and care. These things could be changed by implementing a comprehensive approach to rare diseases, increasing international cooperation in scientific research, by gaining and sharing scientific knowledge about and by developing tools for extracting and sharing knowledge. A significant aspect to analyze is the organization of knowledge in the biomedical field for the proper management and recovery of health information. For these purposes, the sources needed have been acquired from the Office of Rare Diseases Research, the National Organization of Rare Disorders and Orphanet, organizations that provide information to patients and physicians and facilitate the exchange of information among different actors involved in this field. The present paper shows the representation of rare diseases terms in biomedical terminologies such as MeSH, ICD-10, SNOMED CT and OMIM, leveraging the fact that these terminologies are integrated in the UMLS. At the first level, it was analyzed the overlap among sources and at a second level, the presence of rare diseases terms in target sources included in UMLS, working at the term and concept level. We found that MeSH has the best representation of rare diseases terms.